Childhood Emotional Abuse and Depression Among Adolescents: Roles of Deviant Peer Affiliation and Gender - Li, Sen (Journal of interpersonal violence, 2022)
Adolescent depression is a significant concern around the world. There is a pressing need to explore risk factors for this disorder to develop better interventions. Based on an integration of attachment theory, Bronfenbrenner’s ecological systems theory, and relational theory, the current study aimed to examine (a) whether childhood emotional abuse (CEA) would be significantly and positively related to adolescents’ depression, (b) whether deviant peer affiliation would mediate the relation between CEA and depression, and (c) whether gender would moderate the direct and indirect relations between CEA and adolescent’s depression via deviant peer affiliation. Participants were 961 Chinese adolescents (Mage = 15.21 years, SD = 1.57). They completed questionnaires regarding demographics, CEA, other types of childhood maltreatment (i.e., physical abuse, sexual abuse, physical neglect, and emotional neglect), deviant peer affiliation, and depression. Results showed that CEA was positively related to adolescent depression even after controlling for other types of childhood maltreatment, and this relation was mediated by deviant peer affiliation. Furthermore, moderated mediation analyses indicated that gender moderated the relation between CEA and deviant peer affiliation, with the relation being stronger for girls than for boys. However, gender did not moderate the relation between deviant peer affiliation and depression, as well as the direct relation between CEA and depression. Results highlight that interventions aimed at reducing CEA may protect adolescents, especially girls from the risks of deviant peer affiliation and depression.